The Long-term Effects of Percutaneous Laser Disc Decompression (PLDD) Treatment on Lumbar Disc Protrusion: A 2-Year Follow-up - Hashemi, Masoud; Falsafi, Mani; Reza Razzaghi, Mohammad; Dadkhah, Payman; Taheri, Mehrdad; Delshad, Mohammad Hossein; Zali, Alireza (Journal of Lasers in Medical Sciences, 2020)
Introduction: Nowadays many physicians have focused their attention on using low invasive methods for the treatment of disc protrusion. Thus, the current study was carried out to evaluate the effect and therapeutic outcomes of clinical percutaneous laser disc decompression (PLDD) in the treatment of chronic low back pain caused by disc protrusion during a two-year follow-up. Methods: This historical cohort study was conducted on 40 patients, who were suffering from chronic low back pain caused by disc protrusion diagnosed, and referred to the pain clinic of Akhtar Hospital from March to August 2016 were treated with PLDD and were followed up for at least two years after performing PLDD (from 2018 to 2019). All the information has been extracted using medical records and patient interviews. The severity of pain was measured by the Numeric Rating Scale (NRS), and the Oswestry disability index (ODI) was measured before and two years after the treatment. Results: The most common sites for two-level PLDD were L4-S1 and L3-L5, and the most common sites for one-level PLDD were L5-S1 and L4-L5. Overall, the levels of pain and functional disability two years after PLDD showed significant improvements (P = 0.0001). The results revealed no statistically significant differences in NRS and ODI scores between the two groups of men and women two years after PLDD (P > 0.05). Furthermore, they indicated no statistically significant differences in NRS and ODI scores between the different disc protrusion levels two years after PLDD (P > 0.05). Conclusion: It seems that the PLDD is a low-invasive, safe, and effective method that can be used in patients with chronic low back pain caused by a disc protrusion. Therefore, it can be considered as a suitable choice in treating patients with chronic low back pain caused by a disc protrusion